Three-dimensional tracking of motile bacteria near a solid planar surface. - Frymier, P D (1995)
Knowing how motile bacteria move near and along a solid surface is crucial to understanding such diverse phenomena as the migration of infectious bacteria along a catheter, biofilm growth, and the movement of bacteria through the pore spaces of saturated soil, a critical step in the in situ bioremediation of contaminated aquifers. In this study, a tracking microscope is used to record the three-dimensional motion of Escherichia coli near a planar glass surface. Data from the tracking microscope are analyzed to quantify the effects of bacteria-surface interactions on the swimming behavior of bacteria. The speed of cells approaching the surface is found to decrease in agreement with the mathematical model of Ramia et al. [Ramia, M., Tullock, D. L. & Phan-Tien, N. (1993) Biophys J. 65,755-778], which represents the bacteria as spheres with a single polar flagellum rotating at a constant rate. The tendency of cells to swim adjacent to the surface is shown in computer-generated reproductions of cell traces. The attractive interaction potential between the cells and the solid surface is offered as one of several possible explanations for this tendency.